HYDROMINE SOLUTION: OPTIMIZATION TOOLS FOR MINE DRAINAGE AND DEWATERING IN OPEN-PIT MINING - Rahmadani, Fahrul
Mine water can affect various aspects of mining operations, including the efficiency and productivity of equipment and workers, the safety and stability of slopes, and the capital costs associated with mine water pumping. Planning a mine drainage system requires complex calculations, data processing, and precise optimization. Therefore, a supporting tool is needed to expedite this process by utilizing information technology. In this research, the tool was designed using Microsoft Excel software. Microsoft Excel was chosen for its user-friendliness, powerful calculation capabilities, and easy-tounderstand data visualization. The tool produces outputs such as rainfall analysis, the dimensions and capacity of open channels, the dimensions and capacity of culverts, and the dimensions and capacity of sumps along with pump recommendations. Numerical methods are used in the calculation process to obtain the most optimal drainage dimensions. The tool has certain limitations, including the exclusion of groundwater effects and evapotranspiration, preliminary pump recommendations without considering pump efficiency, and the assumption that rainfall is uniformly distributed across all locations. Based on the testing and implementation conducted, this tool produces accurate results consistent with manual calculations and accelerates the calculation process. Therefore, it can be concluded that this tool is designed to support and assist in the planning calculations for open-pit mine drainage systems. Additionally, this tool can aid decisionmaking in determining alternative drainage systems for mines based on the existing considerations.